On Solvability of the Damped Fučík Type Problem with Integral Condition - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2014)
The solvability results are established for the boundary value problem with a damping term , x(0) = 0, where x + = max{x, 0}, x - = max{-x, 0}, h is a bounded nonlinearity, µ, λ real parameters. The existence results are based of the knowledge of the Fučík type spectrum for the problem with h ≡ 0